COMPUTATIONAL METHODS FOR SELECTION OF FUNCTIONAL MONOMERS IN THE SYNTHESIS OF MOLECULARLY IMPRINTED POLYMER OXYTETRACYCLINE - Selvira Anandia Intan Maulidya; Meilia Suherman; Angelika Angelika (Jurnal Ilmiah Farmako Bahari, 2023)
Oxytetracycline is used to treat various disorders in poultry, particularly hens. Their use, however, may be connected with unsatisfactory residual levels in food. Because the generally used method for analyzing oxytetracycline residues is expensive, unique preparation methods such as the Molecularly Imprinted Polymer (MIP) approach have been developed. MIP is one of the most successful pre-analysis preparation procedures for extracting the target analyte from the complicated matrix. The most significant aspect of creating a successful MIP is the selection of functional monomers compatible with the monomer's physicochemical properties and Oxytetracycline as a template. The PyRx and Autodock apps are used in this study to determine the value of the binding affinity and hydrogen bonding created between the functional monomer and the template. According to the study, the monomer 5-[1-(2,3-dimethylphenyl]-1H-imidazole has the lowest binding affinity value (-4.34 kcal/mol), indicating that the Oxytetracycline template will interact well with this monomer.